Why could meditation practice help promote mental health and well-being in aging? - Gaël Chételat; Antoine Lutz; Eider Arenaza-Urquijo; Fabienne Collette; Olga Klimecki; Natalie Marchant (Alzheimer’s Research & Therapy, 2018)
Abstract Psycho-affective states or traits such as stress, depression, anxiety and neuroticism are known to affect sleep, cognition and mental health and well-being in aging populations and to be associated with increased risk for Alzheimer’s disease (AD). Mental training for stress reduction and emotional and attentional regulation through meditation practice might help reduce these adverse factors. So far, studies on the impact of meditation practice on brain and cognition in aging are scarce and have limitations but the findings are encouraging, showing a positive effect of meditation training on cognition, especially on attention and memory, and on brain structure and function especially in frontal and limbic structures and insula. In line with this, we showed in a pilot study that gray matter volume and/or glucose metabolism was higher in six older adult expert meditators compared to 67 age-matched controls in the prefrontal, anterior and posterior cingulate cortex, insula and temporo-parietal junction. These preliminary findings are important in the context of reserve and brain maintenance as they suggest that long-term meditation practice might help preserve brain structure and function from progressive age-related decline. Further studies are needed to confirm these results with larger samples and in randomized controlled trials and to investigate the mechanisms underlying these meditation-related effects. The European Commission-funded project Silver Santé Study will address these challenges by studying 316 older adults including 30 expert meditators and 286 meditation-naïve participants (either cognitively normal or with subjective cognitive decline). Two randomized controlled trials will be conducted to assess the effects of 2-month and 18-month meditation, English learning or health education training programs (versus a passive control) on behavioral, sleep, blood sampling and neuroimaging measures. This European research initiative illustrates the progressive awareness of the benefit of such non-pharmacological approaches in the prevention of dementia and the relevance of taking into account the psycho-affective dimension in endeavoring to improve mental health and well-being of older adults.